PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI SMP - Puteri, Maulidya; Zaura, Bintang; Annisa, Dewi (Jurnal Review Pendidikan dan Pengajaran, 2024)
In mathematics learning, students often face difficulties. One of the causes is the ineffective teaching model used by teachers, resulting in inadequate delivery of learning materials to the students. This study aims to determine whether there is an influence of the PBL model on the learning outcomes of eighth-grade students in class 1 at SMP Negeri 9 Banda Aceh. The approach used in this research is quantitative, and the research type is an experimental study with a true experimental design and a post-test only control format. The population of this study is all eighth-grade students at SMP Negeri 9 Banda Aceh, and the sample consists of students from class VIII 1 (experimental class) and class VIII 2 (control class) selected through random sampling techniques from the four available classes. Data collection was conducted using a test consisting of 5 questions. Questions 1-2 fall under categories C1-C2, questions 3-4 fall under category C3, and question 5 falls under category C4. The analysis of students' mathematics learning outcomes and hypothesis testing used a two-tailed t-test with a significance level of 5% (? = 0.025) and df = 56, resulting in t-calculated ? t-table, which is 6.703 ? 2.003. Based on the data analysis, it can be concluded that the problem-based learning model has an influence on the mathematics learning outcomes of students at SMP Negeri 9 Banda Aceh.